DIAGNOSING AND DEVELOPING THE E-BUSINESS COMPETENCIES OF THE "Z" GENERATION - Czainska, Katarzyna (Management and Administration Journal, 2020)
The purpose of the article is to present an example of a diagnostic tool for identifying the competence gap of representatives of the “Z” generation who want to conduct business in the e-business model. The first part presents the characteristics of the “Z” generation (Gen-Z) based on studies of Polish and foreign literature. Groups of individual professional competences important for e-business owners were also identified, which were developed on the basis of the results of personal research carried out in 2018 by the CAWI method. The methodological part presents the construction and application of the "e_BIS" tool, which can be used to diagnose the current state and development of competences, broken down into competences: business (B), IT (I) and strategic leadership (S). Based on preliminary analyses, it was formulated that the presented tool can be useful both in education (secondary and higher) and on the labour market to properly shape the individual professional competences of representatives of the “Z” generation.